Sexual hormones modulate compensatory renal growth and function - Azurmendi, Pablo Javier (2013)
The role played by sexual hormones and vasoactive substances in the compensatory renal growth (CRG) that follows uninephrectomy (uNx) is still controversial. Intact and gonadectomized adult Wistar rats of both sexes, with and without uNx, performed at 90 days age, were studied at age 150 days. Daily urine volume, electrolyte excretion and kallikrein activity (UKa) were determined. Afterwards, glomerular filtration rate and blood pressure were measured, the kidneys weighed and DNA, protein and RNA studied to determine nuclei content and cell size. When the remnant kidney weight at age 150 days was compared with the weight of the kidney removed at the time of uNx, male uNx rats showed the greatest CRG (50%) while growth in the other uNx groups was 25%, 15% and 19% in orchidectomized, female and ovariectomized rats, respectively. The small CRG observed in the uNx female rats was accompanied by the lowest glomerular filtration value, 0.56 ± 0.02 ml/min/g kwt compared, with the other uNx groups, p < 0.05. Cell size (protein or RNA/DNA) was similar for all the groups except for uNx orchidectomized rats. In this group the cytoplasmatic protein or RNA content was lower than in the other groups while DNA (nuclei content) was similar. Some degree of hyperplasia was determined by DNA content in the uNx groups. Male sexual hormones positively influenced CRG and its absence modulated cell size. Female sexual hormones, instead, did not appear to stimulate CRG. The kallikrein kinin system may not be involved in CRG.